KARAKTERISTIK FLUIDA PEMBAWA MINERALISASI PIT RAMBA JORING DEPOSIT MARTABE, SUMATRA UTARA: MINERALIZATION BEARING FLUID CHARACTERISTIC OF RAMBA JORING PIT MARTABE DEPOSIT, NORTH SUMATRA - Arifin, Asri; Rosana, Mega Fatimah; Yuningsih, Euis Tintin; Yoseph CSSSA, Boy (Buletin Sumber Daya Geologi, 2021)
The research aims to determine hydrothermal evolution of the mineralisation bearing fluid contained in the Ramba Joring Pit, including temperature, pressure, density and depth of mineralisation deposition formation. This research uses the fluid inclusion analysis. Inclusion sampling was carried out on two main textures of ore namely vuggy silica texture formed at range Th 331ºC to 394ºC, Tm -15.19ºC to -12.94ºC with salinity of 14.42 wt% - 14.89 wt%. NaCl equivalent and brecciated texture formed at range Th 287.8ºC – 398.2ºC, Tm -14.89ºC to -11,76ºC and salinity 13.91 wt% – 14.87 wt%. NaCl equivalent. The positive correlation between the homogenization temperature of mineralization formation and salinity of the solution indicates that the leaching process that forms cavities in rocks occurs at the initial stage of the hydrothermal alteration process that begins with the leaching process forming cavities (silica vuggy) followed by the process of silicification with brecciated texture, the deposition of mineralization takes place at this stage. The origin of the solution forms a hydrothermal deposition is a type of basinal water-seawater solution in the form of connate water which is still influenced by surface water/meteoric water, also shows an indication of a relationship with magmatic water. The density of metal-forming fluids ranges from 0.8 gr/cm3 – 0.9 gr/cm3 while the process that takes place in the formation of ore in Ramba Joring Pit is isothermal mixing with a slight warming effect/boiling.